Food borne illness risk factors assessment in UiTM Shah Alam, Malaysia. - Musa, Mushaireen; Jusoff, Kamaruzaman; Khalid, Khazainah; Abd Patah, Mohd Onn Rashdi; Anuar, Jazira; Zahari, Harnizam (IDOSI Publications, 2010)
This study was conducted on 14 food dining halls in UiTM Shah Alam, Malaysia to seek compliance and degree to food safety practices based on Food and Drug Administration, 2004 (FDA) assessment method and practices. The study incorporate interviews, observations, field assessments and discussion with the campus management in order to verify current states and practices. Overall results showed that food safety practices implemented in students’ dining halls in UiTM Shah Alam were at a good level (7 dining halls), satisfactory (6 dining halls) and unsatisfactory (1 dining hall). Food borne illness risk factors that were analyzed include safe food sources, food storing temperature and stock control, personal hygiene, cross contamination and safe food holding temperature. The two risks factors were at an acceptable level; safe food sources and personal hygiene. Safe food sources had achieved 92% and personal hygiene with 92.3% of the compliance level set by the FDA’s Food Safety Risk Level. Other risk factors; food storing temperature and stock control, safe food holding temperature and cross contamination were recorded at 74%, 72.5% and 69.6% of the level set which were out of compliance level based on the FDA assessment.